Craniospinal Irradiation in Adult Medulloblastoma: A Case Report and Analysis of Treatment Planning Comparing Volumetric Modulated Arc Therapy and Three-Dimensional Conformal Radiotherapy - Banjarnahor, Christine Tiarma Ully; Nainggolan, Andreas; Hariyanto, Agustinus Darmadi (Indonesian Journal of Cancer, 2025)
Introduction: Adult medulloblastoma is a very uncommon case. Multimodal treatment, including surgery, radiation therapy, and chemotherapy, has led to an improvement not only in long-term survival but also in major-related toxicity. Case Presentation: We report the case of a 24-year-old man with medulloblastoma who underwent surgery followed by volumetric modulated arc therapy (VMAT) craniospinal irradiation (CSI) three weeks after resection. The radiation dose was 36 Gy in 20 fractions to the craniospinal axis, with an 18 Gy boost dose in 10 fractions to the posterior fossa. Threedimensional conformal radiotherapy (3D-CRT) planning was done to compare the dosimetric results of VMAT and 3D-CRT.Conclusion: The VMAT CSI technique delivers a better dose of homogeneity, conformity, and OARs-sparing than 3D-CRT